The relationship and relativity between three isolates of Potato virus Y Potyvirus infecting potato (Solanum tuberosum L.) at Alexandria and El-Beheira governorates, northern Egypt - Mahmoud H. Abd El-Aziz; S.I. Behiry; H.A. Younes; Karrar A. Hamza (Novel Research in Microbiology Journal, 2019)
Potato virus Y (PVY) is a highly pathogenic virus, causing enormous economic losses in potato (S. tuberosum) crop. Three isolates of PVY were obtained from naturally infected potato plants showing mosaic; yellowing and vein necrosis symptoms, during 2017-2018 growing seasons at certain locations of El-Beheira and Alexandria governorates, Egypt. PVY could be easily transmitted mechanically by aphids. Detection of the PVY3 in different organs of infected Nicotiana glutinosa plants by Indirect-ELISA; Dot blot immunoassay (DBIA) and Tissue blot immunoassay (TBIA), indicated the possibility of using these methods for viral detection. Egyptian PVY (MK376452) isolate was of close homology to PVY isolated from South Africa. The other Egyptian isolates were found to be close to a French PVY (KJ741115) isolate. There were variations on comparing nucleotide and amino acid sequences; however, nucleotide sequencing could be more reliable. Application of sequence inspection allowed us to identify the PVY isolates by phylogenetic analysis. Phylogenetic analysis of the genomic coat protein (CP) from 24 PVY isolates registered in GenBank indicated the presence of relationships between each other's. This reflected the high degree of genetic variability among our local Egyptian isolates. The aims of the current work were to; isolate and detect PVY from naturally infected potato plants in northern Egypt, characterize the PVY isolates using different assays, detect PVY in different organs of infected potato plants, study the CP gene of the PVY isolates using Reverse transcription-Polymerase Chain Reaction (RT-PCR), and register these isolates in GenBank.